Social choices for the next generation of elderly: The combination of resources allocation and the utilization of social conditions - Prasertrungruang, Montree; Ayuwat, Dusadee (International Journal of Engineering and Technology, 2018)
With the advent of the aged society amidst capitalism development, the Next Generation of Elderly (NGE) has the chance to seek social choices. This research relied on the Resource Profile Framework to study the social choices of NGEs under the Capability Approach and the Structuration Approach. The qualitative research method was used with the research target group, or NGEs, who were Thai citizens aged 50 to 59 years residing in an urban and a rural areas of Kud Piang Khom Sub-District, the district of a complete aged society. The data was collected by means of semi-structured interviews from May to September, 2016 with 36 NGEs. Descriptive analysis was conducted to synthesize their social choices. The result showed 5 social choices used by the NGEs: (1) The choice that arises from the use of resource in one dimension for a return of resource in that dimension; (2) The choice that arises from the use of resource in one dimension for a return of resource in another dimension; (3) The choice that arises from the use of resources from many dimensions; (4) The choice that arises from facilitating social conditions; and (5) The choice that arises from integrating personal resources with utilization of facilitating social conditions. NGEsâ€™ social choices were found to vary according to the individuals and community context.Â